Study of fatigue crack growth in al-mg-si alloys using a predictive model under positive and negative load ratios - Espezua, Sandro V.P.; Reis Pereira Baptista, Carlos A.; da Silva Antunes, Ana M.B.; Pastoukhov, Viktor; Torres, Marcelo A. S. [UNESP] (Trans Tech Publications, 2014)
The study of fatigue crack growth (FCG) is aimed at residual life estimations in order to apply the damage tolerant criterion. Usual approaches are based on semi-empirical models that consider the stress intensity factor range of fracture mechanics, DK, as the governing driving force for crack propagation. An alternative approach is the use of predictive theoretical schemes arising from damage mechanics. Although they haven't achieved a reliability level high enough to be used in design, predictive models may be important in some situations like material selection. In the present work, a predictive FCG method based on the cumulative damage of volume elements along the crack path is employed. The development of the work includes considerations about the stress distribution in the cracked body and the stress-life and strain-life relations used in the computational procedure. A previously developed analytical expression for the stress distribution ahead of the crack in a finite width plate, based on the numerical analysis performed by the Finite Element Method, is used in the predictive method. The stress field is determined for both upper and lower limits of cyclic loadings. The fatigue crack growth behavior of three Al-Mg-Si alloys: AA 6005, AA 6351 and AA 6063, tempered and aged for the T6 condition, were analysed for positive and negative R-ratios. In order to check the model results, constant amplitude FCG tests with load ratios ±0.5 were carried out in M(T) specimens. The experimental results, compared to the computational simulations, show that it is possible to obtain predictions of FCG behaviour for both positive and negative load ratios. © (2014) Trans Tech Publications, Switzerland.
Keywords: Aluminium alloys; Crack growth; Fatigue; Modelling